Alternative medicine in aquaculture - TSANTILAS (Η. ΤΣΑΝΤΗΛΑΣ), H.; GOLOMAZOU (Ε. ΓΚΟΛΟΜΑΖΟΥ), E.; ATHANASSOPOULOU (ΑΘΑΝΑΣΟΠΟΥΛΟΥ Φ.), F. (Journal of the Hellenic Veterinary Medical Society, 2017)
The use of alternative treatments in the aquaculture and more generally in production animals has become in our days imperative for important reasons. The common veterinary medicines, that until now were used widely in production animals, have been submitted in strictest controls and legislative restrictions. Furthermore, the overuse of such medicines has led to the creation of resistant bacterial shains, which had as a result the reduction of efficacy of treatments. The use of herbs, i.e. plant organisms with therapeutic attributes, constitutes an alternative treatment, that originates in the culture of many native populations. Their application, however, in fish has appeared only in few the last years and in a limited scale. Nevertheless, the results are satisfactory and encouraging for further experimentations. The probiotics, live microbial supplements of diet, constitute an innovation in the alternative treatments. The use of such substances, since the beginning of the last century, appears to be beneficial in the treatment of various pathological situations and has been applied also in fish. Finally, salt is also included in alternative treatments. The fluctuation of water salinity results in an effective treatment of mainly ectoparasites of fish.